Design, synthesis and structure-activity relationship (SAR) studies of an unusual class of non-cationic fatty amine-tripeptide conjugates as novel synthetic antimicrobial agents - Hernández-Ortiz, Noelia; Sánchez-Murcia, Pedro A.; Gil-Campillo, Celia; Domenech, Mirian; Lucena-Agell, Daniel; Hortigüela, Rafael; Velázquez, Sonsoles; Camarasa, María José; Bustamante, Noemí; de Castro, Sonia; Menéndez, Margarita (Frontiers in Pharmacology, 2024)
Cationic ultrashort lipopeptides (USLPs) are promising antimicrobial candidates to combat multidrug-resistant bacteria. Using DICAMs, a newly synthesized family of tripeptides with net charges from -2 to +1 and a fatty amine conjugated to the C-terminus, we demonstrate that anionic and neutral zwitterionic USLPs can possess potent antimicrobial and membrane-disrupting activities against prevalent human pathogens such as Streptococcus pneumoniae and Streptococcus pyogenes. The strongest antimicrobials completely halt bacterial growth at low micromolar concentrations, reduce bacterial survival by several orders of magnitude, and may kill planktonic cells and biofilms. All of them comprise either an anionic or neutral zwitterionic peptide attached to a long fatty amine (16-18 carbon atoms) and show a preference for anionic lipid membranes enriched in phosphatidylglycerol (PG), which excludes electrostatic interactions as the main driving force for DICAM action. Hence, the hydrophobic contacts provided by the long aliphatic chains of their fatty amines are needed for DICAM's membrane insertion, while negative-charge shielding by salt counterions would reduce electrostatic repulsions. Additionally, we show that other components of the bacterial envelope, including the capsular polysaccharide, can influence the microbicidal activity of DICAMs. Several promising candidates with good-to-tolerable therapeutic ratios are identified as potential agents against S. pneumoniae and S. pyogenes. Structural characteristics that determine the preference for a specific pathogen or decrease DICAM toxicity have also been investigated.